Hubungan Perceived Organizational Support terhadap Kinerja Dokter di Rumah Sakit Kota Makassar - Syahrir Andi Pasinringi; A. Amirah Shalihah; Nurmala Sari (Media Kesehatan Masyarakat Indonesia, 2019)
Doctor is one of professionals who have an important role in the hospital services. Perception ofdoctor related organizational support can build doctor’s trust and performance in hospitals. This study aimsto analyze the relationship of Perceived Organizational Support (POS) on doctor performance in Class BGeneral Hospital of Makassar City. This research is an observational analytic study with cross sectionaldesign. The total sample in this study was 126 respondents selected by simple random sampling technique.Data were analyzed using Pearson correlation test. The results showed that there was a relationship betweenperceived organizational support and doctor performance with a p value of 0,010 < 0,05. POS has arelationship to the performance of doctors so hospitals need to increase the involvement of doctors by creatinga supportive work environment and creating an innovation program to increase doctors’ trust in the hospital.